Direct role of the C-C motif chemokine receptor 2/monocyte chemoattractant protein 1 system in the feline cumulus oocyte complex†. Issue 4 (3rd November 2018) - Rojo, Julieta Laura; Jaworski, Juan Pablo; Peluffo, Marina Cinthia
Abstract: Studies were designed to (a) evaluate the mRNA expression of the C-C motif chemokine receptor 2 ( CCR2 ) and its chemokine ligands, as well as genes related to periovulatory events, within the cumulus oocyte complex (COC) and follicle wall after a luteinizing hormone (LH) stimulus in cultured feline antral follicles; (b) assess the immunolocalization of CCR2 and its main ligand (monocyte chemoattractant protein 1, MCP1) within the feline COC; and (c) examine the direct effects of exogenous recombinant MCP1 on mRNA expression of the CCR2 receptor and MCP1 as well as key periovulatory genes in the COC, using a feline COC culture system. Both culture systems were developed by our laboratory and exhibit physiological response to gonadotropin stimuli. In summary, this study demonstrated mRNA expression of CCR2 receptor and its assessed ligands (MCP1, MCP2, MCP3, and MCP4 ) within the feline COC and follicle antral wall, and a significant increase in CCR2 mRNA by LH within the COC. Also, CCR2 and MCP1 immunoreactivity was observed in the oocyte and cumulus cells of the feline COC. Remarkably, this is the first report, in any species, describing a direct effect of the recombinant MCP1 in the CCR2/MCP1 system within the COC, by increasing the mRNA levels of key genes involved in the ovulatory cascade, as well as its own receptor CCR2 . Together, these data suggest that CCR2 receptor signaling in the COC may regulate events critical for promoting cumulus oocyte expansion and/or oocyte maturation. Abstract : MCP1 directly stimulates the mRNA levels of key ovulatory genes and its own receptor CCR2 within the COC, suggesting that CCR2/MCP1 signaling may regulate events critical for promoting cumulus oocyte expansion and/or oocyte maturation.